Improprieties in Documenting Crime Scene Observations as Cause for Wrongful Convictions - P.T., Jayaprakash (Pusat Pengajian Sains Kesihatan, 2009)
Problem: False accusations and wrongful convictions are victimizations by the investigatory and criminal justice system Remedy: Resorting to scientific observations of crime scenes Objectives I) To elucidate that improprieties in 'observing' crime scenes per se involving equivocal deaths lead to imagine 'homicide' impelling the investigators, prosecutors and judges to accuse/convict an innocent individual wrongfully II) To stress that 'observing' a crime scene in situ is part of forensic science practice and 'crime reconstruction' is the responsibility of the forensic investigator, a forensic science generalist Ill) To recommend the following remedial measures a) rejuvenating 'forensic science generalists' b) inclusion of forensic science crime scene management- as part of the law curriculum